Perceptions of affirmative action and the potential unintended consequences thereof in the work environment : a study of the designated and non-designated groups in South Africa - University of Stellenbosch. Faculty of Economic and Management Sciences. Dept. of Industrial Psychology. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Industrial Psychology))--University of Stellenbosch, 2009.